A comparison of the performance of Riet strategies in South Africa - Kubheka, Ntombenkulu (My University, 2019)
As the objective of investing is the maximization of wealth, it is imperative for investors to find instruments which will help them achieve their goal. A real estate investment trust can be a form of wealth maximization if an investor is knowledgeable about its long-term performance and the drivers of this performance. This study employed the use of panel regression models to isolate the performance of South African REITs, in order to compare the risk-adjusted returns of REIT segments over the long term and to identify the determinants of REIT risk-adjusted returns. Risk-adjusted performance ratios were used to measure return on real estate investment funds to conclude on the performance of SA REITs. The Sharpe ratio, Treynor index and Jensen’s Alpha were performance measures of 55 JSE-listed and delisted REITs over 18 years (2000 – 2017) thus incorporating 433 firm-years.The empirical evidence suggests that size, book-to-market, property asset intensity, dividend yield and real GDP growth influence the performance of South African real estate investment trusts and Hotel and Resort REITs as well as Retail REIT significantly underperformed the other REIT sectors, under the Sharpe ratio and Jensen’s Alpha. Furthermore, the REIT performance during the financial crisis outperformed their performance during the other market phases.
A research report submitted to the Faculty of Commerce, Law and Management, in partial fulfilment of the requirement for the degree of Master of Commerce, University of the Witwatersrand.
Keywords: UCTD; REITs; Sharpe ratio; Treynor index; Jensen’s Alpha; Panel Regression; Real estate investment trusts; Mutual funds--South Africa; SDG-8: Decent work and economic growth